Managerial guidelines to support parents during the hospitalisation of their children in a private paediatric unit - Verwey, M; Jooste, K (Curationis (Pretoria), 2009)
The purpose of this article is to describe managerial guidelines to support parents with the hospitalisation of their child in a private paediatric unit. The hospitalisation of a child is regarded as a major stressor for both parents and child. The role of the family in participating in a child's illness is slowly being recognised (Kibel & Wagstaff 2001:544), but the South African government per se has not yet issued any formal reports on parental participation in the hospitalisation process. The study explored and described the nursing care experiences of parents regarding the hospitalisation of their child in a paediatric unit; managerial guidelines to support parents with their lived experiences of their child's hospitalisation in a paediatric unit. To achieve the purpose and the objectives of the research, an interpretive-phenomenological qualitative approach was used in the research design and methods. Research was conducted through unstructured individual interviews, narrative diaries and field notes and data were analysed through open-coding (Tesch, 1990). Parents were asked to respond to the question "How did you experience your child's hospitalisation in the paediatric ward", followed by probing when the responses of the parents were ambiguous. Purposive sampling was used to achieve saturation of data and seven parents were interviewed and fifteen parents completed narrative diaries. The model of Lincoln and Guba (1985) was used to ensure trustworthiness. Ethical considerations were maintained throughout the study and consent was obtained from the respondents. The recommendations of the research were that attention should be given to 1) empowering parents to participate in their child's care; 2) guiding nursing personnel to plan the discharge process; 3) including parents in the unit routine; 4) fostering a trusting relationship with parents; 5) promoting the communication of information; and 6) creating a therapeutic environment for parents.